Ensino multidisciplinar na melhoria do conhecimento nutricional no ensino fundamental - Lima, Ana Paula Santos de (2014)
Considering the growing concern about the rising rates of obesity in children and adolescents, as well as changes in eating habits, it is necessary to adopt preventive and awareness measures for better quality of life and to implement proper eating habits. For this, multidisciplinary science teaching becomes a key element to help increase nutritional knowledge and change unhealthy eating habits. Thus, school becomes a privileged space to develop health promotion. Teachers have undergone a process of continuing education during the research, this allowed them different interactions with new pedagogical strategies that were used, thus providing they appropriated them. The training provided to teachers to reflect on their practice, resulting in the quality of that education and how it is taught, as well as opportunities for the exchange of experiences, leading changes in their teaching behavior. Therefore, the main objective of this study was to evaluate the advancement of knowledge through nutritional health habits, such as nutritional status, level of nutrition knowledge and dietary practices of primary schools through strategies that allowed to approach these issues in the teaching of school subjects. The research is a case study held in the city of Santa Maria/RS, with students from 6th to 9th grade of a public state school, totaling 175 students. A survey was conducted in order to gather data on body mass index (BMI), weight, height, sex, age, eating habits and nutrition information. From the results obtained, it can be observed that there was an improvement in the nutritional status, as well as in the levels of nutritional knowledge. However, it was also that noticed that the habit of skipping meals is common among students. Therefore, it was verified the importance of creating adequate spaces so that the necessary changes in nutritional status and obesity prevention can occur, in order to achieve so, it is necessary to involve school, families, and community through educational strategies for heal promotion.